Unveiling the true costs and societal impacts of moderate‐to‐severe atopic dermatitis in Europe. (7th July 2022) - Augustin, M.; Misery, L.; von Kobyletzki, L.; Armario‐Hita, J.C.; Mealing, S.; Redding, M.
Abstract: Atopic dermatitis (AD) is a chronic, auto‐immune condition that imposes a high burden on individuals, society, and the healthcare system. Approximately 4.4% of adults and up to 18.6% of children/adolescents have AD in Europe, with 20% of all cases accounting for moderate‐to‐severe forms. This form of the condition in adults results in annual societal costs across Europe of an estimated €30 billion; €15.2 billion related to missed workdays or reduced work productivity, €10.1 billion related to direct medical costs and €4.7 billion related to personal expenditure of patients/families. AD can also substantially impact physical, emotional, and social quality‐of‐life. Several studies have shown the debilitating itch‐scratch cycle is the main cause of the multifaceted burden, as it causes substantial sleep deprivation and stigmatisation due to the physical appearance of the skin, and confidence issues. These factors lead to psychosocial issues and can cumulate over time and prohibit patients reaching their 'full life potential'. Despite this, many patients with the condition are undertreated, resulting in uncontrolled symptoms and a further strain placed on patients, society, and the economy. The authors of this White Paper comprise the European Atopic Dermatitis Working Group, which is a network of international specialists with expertise in dermatology and healthcare policy decisions. Their programme of action is focused on harnessing their expertise to build consensus, advance research, share knowledge, and ultimately seek to improve AD care outcomes through achieving long‐term symptom control. This White Paper presents a systematic evaluation of the overall financial and humanistic burden of moderate‐to‐severe AD and the current challenges that exist with AD care. It introduces recommendations for how, collaboratively, key stakeholders and policy makers can support improvements in AD management to achieve better disease control, thus reducing the costs and associated burden placed on individuals, society, and the economy.